Reduction of Total Harmonic Distortion in Cascaded H-Bridge Inverter by Pattern Search Technique - Suresh N.; R. Samuel Rajesh Babu (Institute of Advanced Engineering and Science, 2017)
Pattern Search technique can be used to find the solution for the optimization problem. In this paper, pattern search algorithm has been utilized to calculate the switching angles for the cascaded H-bridge inverter with the consideration of minimizing total harmonic distortion. Mathematical equations for the optimization problem were formulated by fourier analysis technique. Lower order harmonics such as third, fifth, seventh, ninth and eleventh order harmonics were taken into account to mitigate the total harmonic distortion of the inverter. Simulations have been carried out for thirteen level, fifteen level and seventeen level cascaded H-bridge inverter using matlab software. Total harmonic distortion of voltage and current for resistive load, resistive-inductive load and motor load were analyzed.